2009
DOI: 10.1186/1755-8794-2-54
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125a is over-expressed in insulin target tissues in a spontaneous rat model of Type 2 Diabetes

Abstract: Background: MicroRNAs (miRNAs) are non-coding RNA molecules involved in posttranscriptional control of gene expression of a wide number of genes, including those involved in glucose homeostasis. Type 2 diabetes (T2D) is characterized by hyperglycaemia and defects in insulin secretion and action at target tissues. We sought to establish differences in global miRNA expression in two insulin-target tissues from inbred rats of spontaneously diabetic and normoglycaemic strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 49 publications
(57 reference statements)
2
75
1
1
Order By: Relevance
“…An miR-29 paralog (miR29a) was differentially expressed in visceral adipose tissue between GK and control rats (26), and a series of experiments indicated altered expression of miR-125a in visceral adipose tissue of HFD mice and in 3T3-L1 adipocytes (10). In addition, expression of miR-125a was downregulated in subcutaneous adipose tissue of obese patients, regardless of their diabetes status.…”
Section: Mirna-mediated Regulation Of Insulin Sensitivity In Adipose mentioning
confidence: 91%
See 1 more Smart Citation
“…An miR-29 paralog (miR29a) was differentially expressed in visceral adipose tissue between GK and control rats (26), and a series of experiments indicated altered expression of miR-125a in visceral adipose tissue of HFD mice and in 3T3-L1 adipocytes (10). In addition, expression of miR-125a was downregulated in subcutaneous adipose tissue of obese patients, regardless of their diabetes status.…”
Section: Mirna-mediated Regulation Of Insulin Sensitivity In Adipose mentioning
confidence: 91%
“…Microarray-based profiling of miRNA expression in adipose tissue in animal models and obese patients has provided information on collections of known miRNAs that are differentially expressed in obesity (25,26,51,81), including miRNAs consistently differentially expressed in various rodent models (e.g., miR-27a, miR-103, miR-107) and in both models and humans (e.g., miR-15a, miR-30d). An miR-29 paralog (miR29a) was differentially expressed in visceral adipose tissue between GK and control rats (26), and a series of experiments indicated altered expression of miR-125a in visceral adipose tissue of HFD mice and in 3T3-L1 adipocytes (10).…”
Section: Mirna-mediated Regulation Of Insulin Sensitivity In Adipose mentioning
confidence: 99%
“…Indeed, previous studies have shown that the expression of the miR-125 family is modulated by diabetes. Indeed, miR-125b is upregulated in vascular smooth muscle of diabetic db/db mice (Villeneuve et al 2010) and miR-125a is increased in liver and adipose tissue of diabetic GK rats (Herrera et al 2009). Moreover, an overexpression of miR-125a and miR-125b led to the alteration of insulin signaling pathways by reducing the insulin-dependent Akt and ERK1/2 phosphorylation in SKBR3 cell line (Scott et al 2007).…”
Section: Figurementioning
confidence: 99%
“…Insulin resistance indicates that the peripheral tissues fail to respond to the normal level of insulin, and manifests as an elevated glucose level with decreased insulin-mediated glucose uptake in the skeletal muscle and adipose tissue, and as an impaired suppression of glucose output in the liver (Peppa et al 2010). Herrera et al (2009Herrera et al ( , 2010 profiled a cluster of miRNAs in insulin target tissues in Goto-Kakizaki (GK) rats, a spontaneous rat model of T2D, and found upregulation of miR-222 and miR-27a in adipose tissue; upregulation of miR-125a, miR-195, and miR-103 in liver; and downregulation of miR-10b in muscle.…”
Section: Mirnas and Insulin Resistancementioning
confidence: 99%